The Impact of Disaster Awareness towards Household Disaster Preparedness among Families on the Coast of Banten, Sumur District, Indonesia. Issue 1 (March 2020) - Suryaratri, R D; Akbar, Z; Ariyani, M; Purwalatia, A T; Wahyuni, L D
Abstract: Located in the Ring of Fire, Indonesia has become a country with tectonic and volcanic activity with considerable intensity. One of the impacts of these activities is in the form of a tsunami. In December 2018, a tsunami occurred in Pandeglang, Ujung Kulon, Banten Province with the most victims being in the Sumur District. This research was conducted to determine the level of community awareness and household disaster preparedness in facing disasters. This research is a quantitative study using questionnaires containing statement items to be filled out by respondents. Disaster Preparedness scale form LIPI-UNESCO/ISDR which consists of five aspects and Disaster Awareness scale from Bhat which consists of three aspects were used in this research. There were 166 participants involved in this study. The study suggests that disaster awareness contribute to household disaster preparedness significantly. Meaning that families with high level disaster awareness are more prepared in response to disaster.